2017
DOI: 10.5812/whb.41919
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Breastfeeding Education by Face to Face and Small-Group Education Methods in Mothers’ Self-Efficacy in Kazeroun Health Centers in 2015

Abstract: Background: Education is a process beginning with informing, followed by attitude-making and finally leading to appropriate behavior and performance in trainees. Breastfeeding self-efficacy, as a term, is originated from the social cognitive theory structures of Bandura. This theory refers to one's beliefs and confidence in her/his ability to perform health behaviors like exclusive and successful breastfeeding. Methods: In this study, 270 pregnant women with gestational age over 30 weeks were selected among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Furthermore, another study compared two methods of education (e.g., face-toface and small group education) to assess the effect of educational programs on the possible increase of selfefficacy in exclusive breastfeeding in pregnant mothers. They concluded that the face-to-face education method has positive effects on the infant's feeding pattern, mother's performance, breastfeeding satisfaction, and beliefs, along with self-efficacy (21). Other studies (16m22) reported that the educational intervention improved the performance of breastfeeding in mothers.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, another study compared two methods of education (e.g., face-toface and small group education) to assess the effect of educational programs on the possible increase of selfefficacy in exclusive breastfeeding in pregnant mothers. They concluded that the face-to-face education method has positive effects on the infant's feeding pattern, mother's performance, breastfeeding satisfaction, and beliefs, along with self-efficacy (21). Other studies (16m22) reported that the educational intervention improved the performance of breastfeeding in mothers.…”
Section: Discussionmentioning
confidence: 98%
“…A researcher-made questionnaire was also used for checking the continuation of exclusive breastfeeding (34 yes-no questions), the status of mother-infant rooming-in, infant suckling, the status of the breast, and the way of infant suckling (18 questions), how to breastfeed (6 questions), and the type of breastfeeding (10 questions) that were completed by observing and asking the mother. The scores on the checklist ranged from 0 to 34 marking as poor (0-11), average (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), and favorable (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) performance. Considering that the multiplication and division of scores have no effect on statistical test results, the scores of checklist dimensions were converted to 100, making group comparison easier.…”
Section: Methodsmentioning
confidence: 99%
“…In some studies, the educational group class was offered once and was the main intervention used against the control of standard prenatal care (19,20). Other studies compared different courses of varying length and content against each other, used multiple group educational sessions as an intervention, or included a combination of group classes with additional modes of education delivery (25)(26)(27)32,40). The effect of a 2.5-hour experimental workshop as the intervention for nulliparous women who were already planning to breastfeed was evaluated and an increase in maternal breastfeeding SE was found.…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding education is a process within a program that aims to provide information, shape attitudes, and instill correct behaviors for a speci c purpose and target audience. It can occur individually, in group settings, through clinical training, home visits, and peer education programs [11][12][13] . With the advancement of technology, web-based education, as well as traditional education, is widely used in many elds.…”
Section: Introductionmentioning
confidence: 99%